Sistema de control interno y su incidencia en la recaudación tributaria en la Municipalidad Provincial de Ucayali año 2022 - Ramirez Saavedra, Anita Esther (2024)
The study sought to determine the statistical impact of the internal control system on tax collection in the Provincial Municipality of Ucayali. It was developed under the non-experimental design, at a descriptive and explanatory level, being an applied research. I take as a sample 20 workers whose responsibilities are linked to the tax administration. From the results obtained, it was evident that the internal control system in this municipality is regular, since responsibilities are not assigned in an equitable and clear manner, in addition, sometimes an efficient administration of resources is carried out. Likewise, tax collection is perceived as regular, since the institution does not carry out awareness campaigns and proactive monitoring of debts, as well as the lack of training in collection policy and the absence of procedures and follow-up in collection processes. In general terms, it was established that it has a significant impact on the tax collection of the Provincial Municipality of Ucayali, validated by an R2 of 0.549. At the same time, it was identified that risk assessment is the component with the greatest influence on the collection process, to a lesser extent the rest of the components, despite this, the influence is significant in all of them.